Conformable polyimide-based μECoGs: Bringing the electrodes closer to the signal source. (October 2020) - Vomero, Maria; Porto Cruz, Maria Francisca; Zucchini, Elena; Ciarpella, Francesca; Delfino, Emanuela; Carli, Stefano; Boehler, Christian; Asplund, Maria; Ricci, Davide; Fadiga, Luciano; Stieglitz, Thomas
Abstract: Structural biocompatibility is a fundamental requirement for chronically stable bioelectronic devices. Newest neurotechnologies are increasingly focused on minimizing the foreign body response through the development of devices that match the mechanical properties of the implanted tissue and mimic its surface composition, often compromising on their robustness. In this study, an analytical approach is proposed to determine the threshold of conformability for polyimide-based electrocorticography devices. A finite element model was used to quantify the depression of the cortex following the application of devices mechanically above or below conformability threshold. Findings were validated in vivo on rat animal models. Impedance measurements were performed for 40 days after implantation to monitor the status of the biotic/abiotic interface with both conformable and non-conformable implants. Multi-unit activity was then recorded for 12 weeks after implantation using the most compliant device type. It can therefore be concluded that conformability is an essential prerequisite for steady and reliable implants which does not only depend on the Young's modulus of the device material: it strongly relies on the relation between tissue curvature at the implantation site and corresponding device's thickness and geometry, which eventually define the moment of inertia and the interactions at the material-tissue interface. Graphical abstract: Image 1 Highlights: We have identified key factors for increasing the conformability of PI-based implants and their bio-stability over time. The device thickness should be tailored to the target anatomical area. An open architecture footprint (sieve-like) should be preferred to a solid one. IrOx and PEDOT/PSS are reliable materials for chronic multi-spike recordings. Electrodes with diameter ≤ 100 μm are expected to work similarly in chronic implants.